Some New Results on Vibrational Properties of Amorphous Group IV Semiconductors. (1993) - Caffaro, M. A. Grado; Caffaro, M. Grado
Abstract : For neutron scattering, an interesting formula is derived from the coherent one-phonon dynamic structure factor. In this derivation, phonon density of states is involved; this density is related to spectra due to structural disorder, which is investigated. Our considerations refer to amorphous Group IV semiconductors.